Management of Super-Refractory Status Epilepticus with Isoflurane and Hypothermia - Zhumadilov, Agzam; Gilman, Charles P.; Viderman, Dmitriy (Frontiers in Neurology, 2015)
Super-refractory status epilepticus (SRSE) is defined as status epilepticus that continues 24 h or more after the onset of anesthesia, and includes those cases in which epilepsy is recurrent upon treatment reduction. We describe the presentation and successful management of a male patient with SRSE using the inhaled anesthetic isoflurane, and mild hypothermia (HT). The potential utility of combined HT and volatile anesthesia is discussed.